Tipe Ambiguitas Struktural pada Tulisan Mahasiswa Semester IV Universitas Tadulako - Masyitha Madani; Hasan Basri; Siska Bochari; Hastini Hastini (Jurnal Kreatif Online, 2022)
The study focuses on structural ambiguity that found on students’ writing made by fourth semester students of English Education Study Program in Tadulako University. The objectives of the study are to identify the types of structural ambiguity on the students’ writings and to discover the most dominant type of those structural ambiguities. This study used qualitative research method with descriptive research design. The research sample was 23 students. The sample was chosen by using purposive sampling technique. The data of this study are the sentences contain structural ambiguity in students’ writings. The conclusion of the study are six types of structural ambiguity in the students’ writings, they are VP+NP+PP (2 structures), VP+NP+PP1+PP2 (5 structures), NP+Adj.Clause (1 structure), PP+S / S+PP (more than 1 person in a sentence) is 1 structure, VP+NP+VP: Infinitive+PP1+PP2 (1 structure), VP+PP1+PP2 (2 structures) and the most dominant type is VP+NP+PP1+PP2.